Crystallinity dependence of high-temperature oxidation of silicoboron carbonitride monoliths. (15th July 2021) - Liang, Bin; Zhu, Qishuai; Liao, Xingqi; Liu, Kangwei; Yang, Zhihua; Jia, Dechang; Zhou, Yu
Highlights: Dense, crystallized Si-B-C-N monoliths were oxidized at 1500−1700 °C. Oxidation behavior and kinetics of crystallized Si-B-C-N were studied. A comparative oxidation of crystallized and amorphous Si-B-C-N was firstly reported. Abstract: Comparative investigation of performances of metastable materials in amorphous and crystalline states is pivotal to exploring their applications in engineering. The oxidation behavior and kinetics of the partially crystalline Si2 BC3 N (PCS) monoliths, i.e. amorphous Si2 BC3 N with precipitation of nanocrystallites (10−30 nm) of SiC and BN(C), were investigated at 1500−1700 °C with dwell time ranging from 0.5 h to 16 h. Oxidation leads to the formation of amorphous SiO2 and cristobalite, and more sufficient crystallization of PCS. Due to the release of gases including CO, CO2, N2 and evaporation of B2 O3, PCS undergoes weight loss at 1500−1700 °C. Loose oxide scales with low adhesion strength are formed at 1500−1600 °C, while the scales are highly dense, adherent at 1700 °C indicating good oxidation resistance of PCS. Compared to completely amorphous Si2 BC3 N (CAS), PCS exhibits lower activation energy of ∼50.0 kJ‧mol −1 for 1500−1600 °C/≤16 h, and higher parabolic rate constants (42.5 μm 2 ‧h −1 for 1500 °C/≤16 h, 172.2 μm 2 ‧h −1 for 1600 °C/≤16 h, and 120.4 μm 2 ‧h −1 for 1700 °C/≤4 h), which suggests the inferior oxidation resistance of PCS. One most possible reason is that the changes in superficial chemical compositions and reactivity during crystallization cause larger oxygen uptake on PCS surfaces.